A clinical review on megalencephaly: A large brain as a possible sign of cerebral impairment. Issue 26 (June 2017) - Pavone, Piero; Praticò, Andrea Domenico; Rizzo, Renata; Corsello, Giovanni; Ruggieri, Martino; Parano, Enrico; Falsaperla, Raffaele
Abstract : Abstract: Megalencephaly and macrocephaly present with a head circumference measurement 2 standard deviations above the age-related mean. However, even if pathologic events resulting in both megalencephaly and macrocephaly may coexist, a distinction between these two entities is appropriate, as they represent clinical expression of different disorders with a different approach in clinical work-up, overall prognosis, and treatment. Megalencephaly defines an increased growth of cerebral structures related to dysfunctional anomalies during the various steps of brain development in the neuronal proliferation and/or migration phases or as a consequence of postnatal abnormal events. The disorders associated with megalencephaly are classically defined into 3 groups: idiopathic or benign, metabolic, and anatomic. In this article, we seek to underline the clinical aspect of megalencephaly, emphasizing the main disorders that manifest with this anomaly in an attempt to properly categorize these disorders within the megalencephaly group.